Influence of attentional capture on oculomotor control. - Theeuwes, Jan; Kramer, Arthur F.; Hahn, Sowon (Journal of Experimental Psychology. Human Perception & Performance, 1999)
Previous research has shown that when searching for a color singleton, top-down control cannot prevent attentional capture by an abrupt visual onset. The present research addressed whether a task-irrelevant abrupt onset would affect eye movement behavior when searching for a color singleton. Results show that in many instances the eye moved in the direction of the task-irrelevant abrupt onset. There was evidence that top-down control could neither entirely prevent attentional capture by visual onsets nor prevent the eye from starting to move in the direction of the onset. Results suggest parallel programming of 2 saccades: 1 voluntary goal-directed eye movement toward the color singleton target and 1 stimulus-driven eye movement reflexively elicited by the abrupt onset. A neurophysiologically plausible model that can account for the current findings is discussed. Reprinted by permission of the publisher.